Analisa Tren Skin Care Natural Terhadap Preferensi Konsumen - Andreas Kevin; Clarisa Kusuma; Emiliana Hertati; Kartika Ayu Fitriani; Vincent Wirawan (Universitas Prasetiya Mulya, 2018)
This research is madetoanalyzedtheeffectofnaturalproductstrendtocustomerpreferenceinbuying skin care product. The increasing air pollution has caused facial skin problems such as dull skinand acne. The changing of lifestyles and easiness of information access about health and education nowadays has made people more aware of labels in skin care products. People nowadays started to pay attention to ingredients in skin care products and prefer to buy one with natural ingredients for their daily use. The usage of these natural skin care products are believed to be effective in solving their facial skin problems. Keywords : skin care, natural, pollution, dull skin, acne.